Reliability improvement of multi-phase interleaved DC-DC converters for fuel cell electric vehicle applications - Hicham Mehida; Abdennacer Aboubou; Mohamed Yacine Ayad (Bulletin of Electrical Engineering and Informatics, 2023)
This paper suggests a fast and low-cost method that can be applied in several DC/DC converter topologies for detecting open circuit faults (OCFs) and short circuit faults (SCFs). The suggested method may identify the faults of several power switches even if they occur simultaneously in multi-phase interleaved boost converters (MPh-IBC) by using just the sensors needed to control the converter. This fault detection method (FDM) is based mainly on comparing the measured inductor current and two fault detection thresholds, one for OCFs detection and the other for SCFs detection. This method combined with a corrective strategy to mitigate the negative impacts of OCFs, particularly the significant rise in the ripple of the DC bus voltage and the fuel cell (FC) current, which reduces FC aging and converter reliability. The simulation findings indicate the FDM's excellent performance and speed, as well as its usefulness in detecting defects of many power switches in the converter, with a fault detection time of up to 1.7 µs. The acquired findings further show the excellent effectiveness of the corrective strategy in reducing these ripples in the event of one or two faults.